2014 IEEE Conference on Computer Vision and Pattern Recognition 2014
DOI: 10.1109/cvpr.2014.358
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Optimization of Hierarchical Features for Saliency Prediction in Natural Images

Abstract: Saliency prediction typically relies on hand-crafted (multiscale) features that are combined in different ways to form a "master" saliency map, which encodes local image conspicuity. Recent improvements to the state of the art on standard benchmarks such as MIT1003 have been achieved mostly by incrementally adding more and more hand-tuned features (such as car or face detectors) to existing models [18,4,22,34]. In contrast, we here follow an entirely automatic data-driven approach that performs a large-scale s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
234
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(236 citation statements)
references
References 20 publications
(48 reference statements)
1
234
0
1
Order By: Relevance
“…The included models are Itti et al (1) [here, two implementations have been used: one from the Saliency Toolbox and the variant specified in the graph-based visual saliency (GBVS) paper], Torralba et al (26), GBVS (27), saliency using natural statistics (SUN) (28) (for "SUN, original" we used a scale parameter of 0.64, corresponding to the pixel size of 2.3′ of visual angle of the dataset used to learn the filters; for "SUN, optimal" we did a grid search over the scale parameter; this resulted in a scale parameter of 0.15), Kienzle et al (24,29) (patch size 195 pixels corresponding to their reported optimal patch size of 5.4°). Hou and Zhang (30), AIM (31), Judd et al (23), context-aware saliency (32,33), visual saliency estimation by nonlinearly integrating features using region covariances (CovSal) (34), multiscale rarity-based saliency detection (RARE2012) (35), BMS (5,36), and finally eDN (37). Table S2 specifies the source code used for each model.…”
Section: Methodsmentioning
confidence: 99%
“…The included models are Itti et al (1) [here, two implementations have been used: one from the Saliency Toolbox and the variant specified in the graph-based visual saliency (GBVS) paper], Torralba et al (26), GBVS (27), saliency using natural statistics (SUN) (28) (for "SUN, original" we used a scale parameter of 0.64, corresponding to the pixel size of 2.3′ of visual angle of the dataset used to learn the filters; for "SUN, optimal" we did a grid search over the scale parameter; this resulted in a scale parameter of 0.15), Kienzle et al (24,29) (patch size 195 pixels corresponding to their reported optimal patch size of 5.4°). Hou and Zhang (30), AIM (31), Judd et al (23), context-aware saliency (32,33), visual saliency estimation by nonlinearly integrating features using region covariances (CovSal) (34), multiscale rarity-based saliency detection (RARE2012) (35), BMS (5,36), and finally eDN (37). Table S2 specifies the source code used for each model.…”
Section: Methodsmentioning
confidence: 99%
“…Such models dramatically improved the visual attention. Vig et al [95] proposed the first deep learning saliency model, which incorporated biologically inspired features, and used the standard learning pipeline. Kummerer et al [96] presented a novel way to reuse existing object recognition neural networks for fixation prediction.…”
Section: ) Bayesian Modelsmentioning
confidence: 99%
“…One of the first attempts to leverage deep learning for saliency prediction was Vig et al [14], using convnet layers as feature maps to classify fixated local regions. Kümmerer et al [15] introduced the model DeepGaze, built on top of the AlexNet image classification network [16].…”
Section: Related Workmentioning
confidence: 99%